Flame Stabilization In Multiple Inlet Channel Meso-Scale Tube Combustors With Wire Mesh - Abdul Munir, Fudhail; Mikami, Masato; Hassan, Muhammad Zahir; Salim, Mohd Azli (Akademia Baru, 2017)
Micro combustion system is one of potential solutions that provides better energy requirement for small-scale devices as compared to conventional batteries. Very recently, quite a number of works have been performed to enhance the combustion stability of meso and micro-scale combustors. Researchers and engineers are diligently experimenting various design of micro combustors with the ultimate objective of having reliable burner. In this study, a meso-scale tube combustor with multiple inlet channel is proposed. Stainless steel wire mesh is utilized as the flame holder, which is located between the unburned and burned gas region. The combustion take place in a channel with 3.5 mm diameter. Aluminium is selected as the material of the combustor considering the limitation of fabrication technology. A three dimensional (3-D) model is utilized to demonstrate the combustion of propane-air mixture in the designed combustor. The results in terms of streamline velocity pattern, heat of reaction, wire mesh and outer wall temperature are established. It is shown in this paper that flame can be stabilized in the tube combustor. Nevertheless, the proposed combustor is only at a preliminary design where there are quite a number of important parameters that need to be obtained before going into fabrication stage. One of the important examples is flame blow out limits.